Presentation of the Citizens’ administrative law circle - Nikolova, Raina (Law Journal of New Bulgarian University, 2022)
The Citizens’ administrative law circle is a first of its kind non-lecture initiative for the students at the Master’s Program in Law of the New Bulgarian University who are interested in the administrative rights and obligations of citizens. It aims to unite the aspirations of future lawyers to acquire specialized scientific knowledge about the administrative legal status of the individuals; to provoke their increased interest in discussing issues affecting the personal, political, economic, social and cultural administrative rights and obligations of citizens; to develop the intellectual potential of its participants by stimulating the creative impulses of some of them to produce publications; to become an influential forum and an authoritative intellectual centre for the curious and educated members of the University’s student, academic and scientific community.